A call for better doctor–nurse collaboration: A qualitative study of the experiences of junior doctors and nurses in escalating care for deteriorating ward patients. Issue 1 (January 2020) - Chua, Wei Ling; Legido-Quigley, Helena; Jones, Daryl; Hassan, Norasyikin Binte; Tee, Augustine; Liaw, Sok Ying
Abstract: Background: Despite the widespread implementation of medical emergency teams (METs) in hospitals to provide immediate interventions to deteriorating ward patients, little is known about how junior doctors and nurses escalate care for deteriorating ward patients in hospitals with established MET services. Objectives: The objective of this research study was to explore the experiences of junior doctors and nurses in escalating care for clinically deteriorating patients in general wards. Methods: Twenty-four individual interviews were conducted with 10 junior doctors and 14 registered nurses of a 1000-bed acute general hospital with the most established MET service in Singapore. Interviews were transcribed verbatim and analysed using an interpretive thematic analysis approach. Findings: Three salient themes emerged from thematic analysis: (1) MET activations versus the primary team doctors' reviews, (2) challenges in obtaining medical reviews, and (3) unspoken rules of the escalation of care. Participants' decisions to call the MET or to escalate to the primary team doctors not only depended on the severity of a patient's deterioration and their perceptions of the primary team doctors' capacity to manage the patient but also were largely influenced by sociocultural factors that were shaped by the hierarchy of medical professions. Key challenges faced by nurses in obtaining medical reviews from junior doctors for patients with early deterioration included presenting "convincing" evidence of patient deterioration and "packaging" information about patient deterioration. Conclusions: The decision to call a MET or the primary team doctors is a complex judgement that is greatly influenced by the dynamics of perceived hierarchy between the medicine and nursing professions and within the medicine profession. Educational and organisational changes that enhance doctor–nurse interprofessional and intraprofessional collaboration among all levels of doctors may improve the process of the escalation of care for deteriorating patients and thus improve patient safety for hospitalised patients.